TANTANGAN DAN STRATEGI PENGINTEGRASIAN ILMU RUMPUN IPS DALAM PEMBELAJARAN DI PGMI : MEMBANGUN KOMPETENSI GURU UNTUK PENDIDIKAN BERKUALITAS - Defirra Alizunna; Fatikh Inayahtur Rahma (PGMI UNHASY, 2024)
This article discusses the challenges and strategies of integrating Social Studies in Madrasah Ibtidaiyah (PGMI) Teacher Education learning with a focus on discussing the complexity of social studies materials, differences in student learning styles, and learning accessibility gaps. Analysis of the literature reveals that teachers face difficulties in bridging the division between social studies content and Islamic values, requiring specific strategies to create an integrated learning experience. In this context, the main strategies proposed involve the application of technology in teaching to link social studies materials with Islamic values, curriculum development that is responsive to student diversity, and learning differentiation strategies that suit individual needs. This article aims to provide practical guidance for teachers, researchers and policy makers in facing the challenges of integrating social studies in the school environment, building teacher competencies and creating classrooms that integrate diversity as a valuable resource. The conclusion of this article is expected to make a significant contribution to the development of future strategies in achieving quality social studies education.